2004
DOI: 10.1074/jbc.m313748200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Group V Phospholipase A2 in Zymosan-induced Eicosanoid Generation and Vascular Permeability Revealed by Targeted Gene Disruption

Abstract: Conclusions regarding the contribution of low molecular weight secretory phospholipase A 2 (sPLA 2 ) enzymes in eicosanoid generation have relied on data obtained from transfected cells or the use of inhibitors that fail to discriminate between individual members of the large family of mammalian sPLA 2 enzymes. To elucidate the role of group V sPLA 2 , we used targeted gene disruption to generate mice lacking this enzyme. Zymosan-induced generation of leukotriene C 4 and prostaglandin E 2 was attenuated ϳ50% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
155
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 53 publications
6
155
1
5
Order By: Relevance
“…Note Added in Proof-Recently, Arm and co-workers have shown that disruption of the mouse group V sPLA 2 gene leads to an ϳ50% reduction in the amount of arachidonic acid liberated from zymosanstimulated peritoneal macrophages (58), and yet earlier studies showed that the disruption of the cPLA 2 -␣ gene leads to complete loss of arachidonic acid from these cells (59). Thus, it appears that group V sPLA 2 action somehow augments the function of cPLA 2 -␣ in peritoneal macrophages.…”
mentioning
confidence: 99%
“…Note Added in Proof-Recently, Arm and co-workers have shown that disruption of the mouse group V sPLA 2 gene leads to an ϳ50% reduction in the amount of arachidonic acid liberated from zymosanstimulated peritoneal macrophages (58), and yet earlier studies showed that the disruption of the cPLA 2 -␣ gene leads to complete loss of arachidonic acid from these cells (59). Thus, it appears that group V sPLA 2 action somehow augments the function of cPLA 2 -␣ in peritoneal macrophages.…”
mentioning
confidence: 99%
“…Construction of the GV sPLA 2 -deficient mouse line, backcrossed to the C57BL/6 background for 10 generations, was carried out as described (16). Heterozygous breeding pairs (GV ϩ/Ϫ ) were used to generate GV Ϫ/Ϫ and GV ϩ/ϩ littermates.…”
Section: Methodsmentioning
confidence: 99%
“…The functional importance of GV sPLA 2 in eicosanoid biosynthesis is established by the observations that LTB 4 and PGE 2 production is ϳ50% lower in macrophages from mice with targeted deletion of GV sPLA 2 (GV Ϫ/Ϫ mice) than from GV ϩ/ϩ mice (16) and that BAL fluid from mice that overexpress GV sPLA 2 contains about 2-fold more PGE 2 than wild type mice (14). sPLA 2 enzymes also regulate biological responses by generating 1-Oalkyl-lysophosphatylcholine, the precursor of platelet activating factor (17), and through binding to specific mannose-type sPLA 2 receptors (18,19).…”
mentioning
confidence: 99%
“…The concentration of LTC 4 secreted during eosinophil activation was assayed by competitive enzyme immunoassay (Cayman Chemicals) using a method that we have reported previously (20,33,34). A total of 21 eosinophil isolations from different donors were used in this protocol.…”
Section: Determination Of Ltc 4 Secretion By Elisamentioning
confidence: 99%